Finite Element Analysis on Cube and Prism Beam of Ceramic Waste Concrete - Che Rosely, Noor Ain Najihah; Wan Amizah Binti Wan Jusoh; Mohamad Hairi Bin Osman (Progress in Engineering Application and Technology, 2021)
Ceramic and sanitary waste is typically produced from industries in which it occurred before and during the phase of manufacturing due to flaws in design, human negligence or even insufficient raw supplies. Enormous quantity of ceramic waste, leads to damage of environment. This study was aim to develop model for series of cube and prism beam of ceramic waste using Abaqus 6.14 software. Another objective was to analyse compression and flexural behaviour of ceramic waste concrete under load. This paper was conducted by collecting data of ceramic concrete density, modulus elasticity, compressive strength and flexural strength from previous study. Concrete grade 30 N/mm2 has been used for concrete control (CC) and other ceramic waste coarse aggregate concrete with partial replacement of coarse aggregate 25%, 50% and 75% (CCA 25, CCA50 & CCA75). Data of ceramic concrete density and modulus elasticity were essential elements to be put in the Abaqus simulation in order to design both models of cube with size of 150x150x150mm and prism beam with dimension of L=700mm, W=150mm, D=150mm. From both two model’s simulation in this paper, cube and prism beam, prism beam produced the same pattern result as the previous study, which means highest compressive strength at 75% partial replacement. While for cube model, resulted in the opposite way where 75% partial replacement produced the lowest compressive strength.